Didactic sequences for teaching and assessing comics reading - Alves-Costa, Lucas Piter; Oliveira, Mayara Victória dos Santos; Rodrigues, Arthur Schitine Siqueira (9 Arte (São Paulo), 2023)
It aims to propose a didactic sequence for the teaching and evaluation of critical reading of comics, considering some skills foreseen in the BNCC. The methodology is based on Semiolinguistic Discourse Analysis (Charandeau, 2008), with theoretical appropriations from Ramos (2009), Groensteen (2015), Joly (2007), Kleiman (2002), Dell'Isola (1996), Dolz, Noverraz, Schneuwly (2004). The material used for the didactic sequence are a cartoon by Mau. We defend that the course of reading aims not only at understanding, but at giving meaning to the world. The results suggest that reading comics in schools is still a challenge, due to the lack of familiarity with the semiotic system of these genres.